Erythema Nodosum Leprosum in Lepromatous Type Hansen’s Disease: A Case Report - Utomo, Zulfikri Firmansyah Prayitno; Widiatma, Ridha Ramadina (Faculty of Medical - UPN Veteran Jawa Timur, 2025)
This case report describes a 39-year-old woman with lepromatous Hansen's disease accompanied by erythema nodosum leprosum (ENL) reaction. The patient had complained of lumps in the facial area since 2017 and did not experience any improvement after therapy. In 2022, the diagnosis of ENL was confirmed by BTA examination with a bacterial index of +1 and a morphological index of 90%. After undergoing one year of therapy and re-evaluation, an increase in morphological index was found. Currently, the lesions have spread to the hands and feet, and the patient is receiving anti-inflammatory and supportive therapy with regular monitoring. ENL is a type II reaction to immune-mediated Hansen's disease with the role of various inflammatory cytokines. Risk factors include lepromatous type, hormonal status, and bacterial index. Delayed diagnosis and suboptimal therapeutic response can worsen the clinical course. In conclusion, this case highlights the importance of early detection, immunological management, and a multidisciplinary approach in managing chronic ENL in lepromatous Hansen's disease.